(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The research aims to identify the level of school violence prevalence among students of Lattakia city schools (second cycle) of grades (seventh, eighth and ninth), in addition to identifying the differences in the level of school violence according to a set of variables (gender, academic achievement, school gender, grade). The research sample included (250) male and female students from the schools of the city of Lattakia from grades (seventh, eighth, and ninth). For the research tools, the school violence scale was applied (prepared by the researcher). The results showed that the prevalence of school violence among students was as follows: the largest percentage of the sample members were within the low level with a percentage of (57.2%), and a small percentage of the sample members (38%) were in the medium level, and (4.8%) were within the high level of the prevalence of violence in the school, and the results showed that there were statistically significant differences in the level of school violence according to the gender variable in favor of male students, and there were also statistically significant differences according to the academic achievement variable in favor of students with low achievement, while the results showed no differences Statistical function according to the variables of school gender and grade.